2022
DOI: 10.1186/s13063-022-06352-3
|View full text |Cite
|
Sign up to set email alerts
|

The NICU Antibiotics and Outcomes (NANO) trial: a randomized multicenter clinical trial assessing empiric antibiotics and clinical outcomes in newborn preterm infants

Abstract: Background Early-onset sepsis is an important cause of neonatal morbidity and mortality in the preterm population. Infants perceived to be at increased risk for early-onset sepsis are often treated empirically with broad-spectrum antibiotics while awaiting confirmatory blood cultures, despite an overall incidence of early-onset sepsis of 2–3% among extremely-low-birthweight (ELBW) infants. Recent observational studies associate perinatal antibiotic use with an increased incidence of necrotizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Ultimately, the inherent limitations of existing human studies warrant large prospective RCTs ( 105 ) as well as well-designed prospective observational studies ( 106 ) to study the impact of withholding early antibiotic use or limiting duration of exposure on NEC as well as other outcomes including late-onset sepsis and bronchopulmonary dysplasia. The NICU Antibiotics and Outcomes Trial (NANO) as well as other studies are beginning to address this question ( 106 108 ). Future clinical practice on early antibiotics use will likely be impacted by these ongoing studies.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Ultimately, the inherent limitations of existing human studies warrant large prospective RCTs ( 105 ) as well as well-designed prospective observational studies ( 106 ) to study the impact of withholding early antibiotic use or limiting duration of exposure on NEC as well as other outcomes including late-onset sepsis and bronchopulmonary dysplasia. The NICU Antibiotics and Outcomes Trial (NANO) as well as other studies are beginning to address this question ( 106 108 ). Future clinical practice on early antibiotics use will likely be impacted by these ongoing studies.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…This would only be possible with a prospective study design. In this regard, the NICU Antibiotics and Outcome (NANO) trial is currently recruiting for a placebo-controlled prospective randomised trial investigating the effect of early empirical antibiotic therapy, which may provide answers 50. Another limitation is that our dataset was not complete.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the NICU Antibiotics and Outcome (NANO) trial is currently recruiting for a placebo-controlled prospective randomised trial investigating the effect of early empirical antibiotic therapy, which may provide answers. 50 Another limitation is that our dataset was not complete. For most variables we used for our analyses, there were significantly less than 10% missing values.…”
Section: Original Researchmentioning
confidence: 99%
“…Judicious antibiotic use in preterm infants, given their frequent empirical antibiotic treatment, can positively impact gut microbiota and subsequent neurocognitive outcomes [ 45 ]. In an observational study – with inherent limitations and therefore not proving causation – we observed that prolonged empirical antibiotic treatment in preterm infants was associated with below-average gross-motor development at 24 MCA [ 46 ].…”
Section: Modulating Gut Microbiota For Neurodevelopmentmentioning
confidence: 99%